A brief review of Lynch syndrome: understanding the dual cancer risk between endometrial and colorectal cancer - Pallatt, Sneha; Nambidi, Sibin; Adhikary, Subhamay; Banerjee, Antara; Pathak, Surajit; Duttaroy, Asim K. (Oncology Reviews, 2025)
Lynch syndrome (LS) is an autosomal dominant disorder caused by germline mutations in DNA mismatch repair (MMR) genes. These mutations result in frameshift alterations, leading to the accumulation of errors within microsatellites. Individuals with LS have an elevated risk of developing colorectal and distant malignancies, including endometrial cancer (EC), which is one of the most common cancer associated with LS. Despite its significance, the association between EC and LS is often underexplored. Given the slow progression of colorectal cancer (CRC), there is an opportunity for early detection and intervention, which can aid in reducing both incidence and mortality through the identification and management of pre-malignant lesions and early-stage tumors in colorectum/endometrium. Recognizing individuals with a heightened risk of CRC is essential for implementing personalized screening strategies. This review summarizes the original research work on LS to find out the correlation of CRC following an endometrial cancer diagnosis in individuals with MMR gene mutations, may involve refine treatment strategies and moreover this review may help clinicians and researchers to get an up-to date information on LS and its advanced treatment possibilities.